Synergistic catalyst, its preparation method and application
By constructing a core-shell synergistic catalyst, with an inorganic oxide core and a specific catalytic element in the shell, the problem of high yield and output ratio control in the production of acrylonitrile in the existing technology has been solved, realizing efficient and simple production of acrylonitrile and hydrogen cyanide.
Patent Information
- Application Number
- CN202610389057.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-27
- Publication Date
- 2026-07-10
AI Technical Summary
Existing technologies in acrylonitrile production processes are difficult to achieve high yields and flexible control of output ratios, and require demanding equipment or involve cumbersome processes.
The core-shell synergistic catalyst has an inorganic oxide core and a shell containing catalytically active components such as iron, molybdenum, zinc, titanium, potassium, antimony, and nickel. By controlling the particle size and compactness, the stability and activity of the catalyst in the fluidized bed process are ensured. Combined with the synergistic effect of specific elements, the catalytic efficiency is improved.
It enables flexible control of high yield and output ratio of acrylonitrile and hydrogen cyanide in fluidized bed processes, is simple to operate, adapts to existing process systems, and reduces equipment requirements and process complexity.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a synergistic catalyst, its preparation method, and its application. Background Technology
[0002] In the C3 industrial chain, the ammonia oxidation reaction of propylene as a raw material to produce acrylonitrile is a crucial step. The byproduct, hydrogen cyanide, also has commercial value. Therefore, the goal is to maintain high yields of both products in this production process, and to allow for real-time adjustment of the output ratio to adapt to changing market demand and commodity prices (e.g., increasing the proportion of hydrogen cyanide produced in the reaction to meet increased demand). Currently, some technologies, based on process and equipment development, can achieve certain yield improvements and output ratio adjustments. However, these technologies have stringent requirements for equipment or process design, or involve overly complex production steps and high investment costs. Summary of the Invention
[0003] Based on the shortcomings of existing technologies, the purpose of this invention is to provide a synergistic catalyst. By constructing a core-shell structure and introducing specific catalytic elements, while controlling the size and density of the product, when this product is applied to the production of acrylonitrile and hydrogen cyanide, it is not only fully compatible with existing fluidized bed process systems, but also has low operation difficulty and simple process. Furthermore, the acrylonitrile and hydrogen cyanide produced have high yields, and the output ratio can be controlled according to actual needs.
[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A synergistic catalyst includes composite particles comprising a core and a shell; The core comprises inorganic oxides; The outer shell includes catalytically active components; the catalytically active components include iron, molybdenum, zinc, titanium, potassium, antimony, and nickel. The particle size D of the composite particles v50 The size ranges from 20 to 100 μm, and the density ranges from 0.8 to 1.8 g / mL.
[0005] To achieve the controllable and high-yield requirements of existing technologies for the production ratio of acrylonitrile and hydrogen cyanide in fluidized bed processes, this invention provides a synergistic catalyst based on an existing production process system. This synergistic catalyst product, with a core-shell structure and an inert, non-organic inorganic oxide core, exhibits high relative stability in reaction systems containing organic raw materials. Simultaneously, it provides high internal support to the outer shell. Compared to traditional core-shellless carrier systems, this avoids internal collapse due to pressure in fluidized bed processes, thus mitigating the impact of internal collapse. To enhance catalytic performance, specific control is applied to the particle size and density of the composite particles. This balances the stability and dispersion of the synergistic catalyst in the fluidized bed, preventing uneven fluidization or loss due to entrainment by the gas phase, and ensuring stable fluidization during catalysis. At the specified particle size and density, the internal diffusion path and actual bed density of the particles in contact with the reactants are moderate, resulting in high packing dispersion, high consistency of reactants in contact with the synergistic catalyst, and high reactivity. Furthermore, the synergistic catalyst exhibits dispersed packing stress, high structural stability during catalysis, and is not easily broken.
[0006] Meanwhile, under the aforementioned structure, the product uses a complex of iron, molybdenum, zinc, titanium, potassium, bismuth, and nickel as its catalytic active system. Each element plays an indispensable key role: molybdenum can adsorb oxygen during the reaction stage, converting it into lattice oxygen and transferring it to further oxidation reactions, serving as a framework component; iron promotes the rapid migration of lattice oxygen, preventing excessive reduction and deactivation on the product surface, stabilizing the crystal structure of the catalytic components, and working with the core to prevent internal collapse of particles; in the presence of nickel, it can form a specific iron-nickel-like solid solution, regulating the redox potential and accelerating the reaction; zinc provides amphoteric centers, not only altering the surface electronic environment but also regulating the active pathway of the reaction; titanium has high surface energy and can act as an anchor point to enhance the binding tightness of the catalytic components. Together with potassium and antimony, it improves the overall catalytic efficiency, activity, and binding stability of the catalytic active components from multiple dimensions, balancing high catalytic activity and long service life. The absence of any one of these elements or its replacement will lead to a significant decrease in product performance.
[0007] Preferably, in the core, the inorganic oxide includes at least one of silicon dioxide and aluminum oxide.
[0008] As described above, the core of the product described in this invention is mainly designed to ensure the product's relative stability in the organic raw material reaction system and to provide internal support, thereby inhibiting the collapse of product particles due to reaction or external forces during the reaction process. Based on this, those skilled in the art can choose inorganic oxide components commonly used in the field of catalysts, such as silicon dioxide, as the core component. In addition, those skilled in the art can also choose to use other types of inorganic oxides based on actual needs, as long as they do not affect the role of the catalytically active components in the outer shell and can achieve the expected effect of the core.
[0009] Preferably, the outer shell further includes a carrier, which includes at least one of silicon dioxide and aluminum oxide.
[0010] When the synergistic catalyst described in this invention is used, the catalytically active component is mainly concentrated in the outer shell of the particle. Under the premise of ensuring the normal activity of the catalytically active component, those skilled in the art can use common inactive carrier components, such as silica or alumina mentioned above, to support the catalytically active component and fix it, but are not limited to this. Those skilled in the art can also use other types of substances as carriers to construct the outer shell based on the actual situation.
[0011] Preferably, the synergistic catalyst comprises the following elements in parts by weight: Si and / or Al 5~25 parts, Fe 20~45 parts, Mo 1~25 parts, Zn 1~15 parts, Ti 1~15 parts, K 1~12 parts, Sb 0.1~12 parts, Ni 0.1~12 parts.
[0012] In some embodiments, the weight parts of Si and / or Al are 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 20 parts, 25 parts, or any two of these values; the weight parts of Fe are 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, or any two of these values; the weight parts of Mo are 1 part, 2 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, or any two of these values; the weight parts of Zn are 1 part, 2 parts, 5 parts, 8 parts, 10 parts, 15 parts, or any two of these values; and the weight parts of Ti are 1 part. The weight of K is within the range of one or any two of the following: 1 part, 2 parts, 5 parts, 10 parts, 15 parts; the weight of Sb is within the range of one or any two of the following: 1 part, 2 parts, 3 parts, 5 parts, 6 parts, 8 parts, 9 parts, 10 parts, 12 parts; the weight of Ni is within the range of one or any two of the following: 0.1 parts, 0.2 parts, 0.5 parts, 1 part, 2 parts, 3 parts, 5 parts, 6 parts, 8 parts, 9 parts, 10 parts, 12 parts.
[0013] Preferably, in the synergistic catalyst, the metal element in the catalytically active component exists in the form of metal oxides and / or metal salts.
[0014] More preferably, the catalytically active component includes metal oxides and metal salts, wherein the metal oxides account for ≥60% by mass in the catalytically active component.
[0015] More preferably, the synergistic catalyst also contains a valence equilibrium element, which refers to the corresponding element in the metal or non-metal compound of the synergistic catalyst of the present invention used to balance the valence state of the metal or non-metal. For example, if Si and / or Al exist as oxides as mentioned above, then the corresponding valence equilibrium element in the compound is O. When the metal element in the catalytic active component exists as a metal oxide, the corresponding valence equilibrium element is O. When it exists in the form of a metal salt, such as zinc in the form of zinc chloride, the corresponding valence equilibrium element is Cl. There is no specific limitation on this. Its type is related to the raw materials or preparation process of the corresponding metal or non-metal element. However, these elements usually do not affect the catalytic activity and structural stability of the product.
[0016] More preferably, the valence equilibrium element includes at least one of O, C, Cl, Br, S, F, and N.
[0017] More preferably, the synergistic catalyst includes X a Fe b Mo c Znd Ti e K f Sb g Ni h Y i Where X is at least one of Si and Al, Y is at least one of O, C, Cl, Br, S, F, and N, 0.17≤a≤0.93, 0.35≤b≤0.81, 0.01≤c≤0.27, 0.01≤d≤0.23, 0.02≤e≤0.32, 0.02≤f≤0.31, 0.0001≤g≤0.1, 0.001≤h≤0.2, and i is the number of atoms required to satisfy the valence requirements of the other elements present.
[0018] More preferably, the synergistic catalyst comprises, per 100 parts, the following elements by weight: 10-20 parts Si and / or Al, 25-40 parts Fe, 5-20 parts Mo, 1-10 parts Zn, 1-10 parts Ti, 1-9 parts K, 0.1-9 parts Sb, 0.1-9 parts Ni, and 15-40 parts of valence equilibrium elements.
[0019] In the synergistic catalyst, the ratio of Fe to Mo elements affects the catalytic production of acrylonitrile and hydrogen cyanide. When the ratio of Fe to Mo, along with other elements, is preferably within the above-mentioned range, the catalytic activity of the synergistic catalyst for acrylonitrile and hydrogen cyanide can be improved simultaneously, resulting in a higher catalytic yield.
[0020] It should be noted that the synergist of the present invention also contains an unavoidable amount of impurities, which refers to impurity elements that are unavoidably introduced during product production or raw material supply, other than the metal or non-metal elements mentioned above and their corresponding valence equilibrium elements.
[0021] More preferably, the impurity has a weight fraction of ≤0.1 parts.
[0022] More preferably, the synergistic catalyst comprises, per 100 parts, the following elements by weight: 12-18 parts Si and / or Al, 27-35 parts Fe, 12-16 parts Mo, 2-5 parts Zn, 2-4 parts Ti, 1.2-4 parts K, 0.5-5 parts Sb, 0.3-6 parts Ni, and 16-35 parts of valence equilibrium elements.
[0023] When the elemental distribution ratio of the synergistic catalyst is preferably set within the above range, especially when the elemental ratio of Fe and Mo is controlled within the above range, the product has better catalytic activity and higher catalytic efficiency, which is more conducive to improving the yield of acrylonitrile and hydrogen cyanide.
[0024] It should be noted that the elemental weight parts of the synergistic catalyst described in this invention are confirmed in the following manner: Disperse 1g of composite particles in 20mL of water, add 10mL of aqua regia, mix thoroughly, and then microwave until the composite particles are completely dissolved. Dilute the solution to 100mL with water to obtain the test solution. Perform ICP testing on the test solution. Before testing, a standard solution must be prepared. The linear correlation coefficient of the standard concentration must be above 0.999 to be used as a normal standard. Dilute the 1000 mg / L standard solution with deionized water to different concentrations (0, 1 mg / 100mL, 2 mg / 100mL, 3 mg / 100mL), and select the element detection wavelength. Set the experimental conditions: use an ICP inductively coupled plasma atomic emission spectrometer; operating conditions: gas flow rate 0.5L / min, power 1150W; select the target element detection wavelengths (Si, Al, Fe, etc.); and use the self-analysis function of the ICP testing software to determine the element content in the sample, in ppm. The standard solution refers to a solution containing the element to be tested. Standard solutions are commercially available, and the results are converted to the weight parts of each element.
[0025] In some embodiments, the particle size D of the composite particles v50 The range of values is one or any two of the following: 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, and 100μm.
[0026] More preferably, the particle size D of the composite particles v50 It is 40~80μm.
[0027] When the particle size D of the composite particles v50 When further optimized within the above-mentioned range, it can achieve better dispersion and contact reaction effects when applied to the catalytic reaction process of fluidized bed technology, while also exhibiting better stability and overall better performance.
[0028] It should be noted that the particle size D of the composite particles described in this invention v50 The particle size D is determined by confirming the particle size distribution using a Malvern laser particle size analyzer (non-sedimentation method). The particle size at which the cumulative volume distribution reaches 50% is considered the particle size. v50 .
[0029] In some embodiments, the compactness of the composite particles is a range of one or both of the following: 0.8 g / mL, 0.9 g / mL, 1 g / mL, 1.1 g / mL, 1.2 g / mL, 1.3 g / mL, 1.4 g / mL, 1.5 g / mL, 1.6 g / mL, 1.7 g / mL, and 1.8 g / mL.
[0030] More preferably, the density of the composite particles is 1~1.5 g / mL.
[0031] When the density of the composite particles is further preferably within the above range, the product has a better stacking effect when applied to fluidized bed catalytic reactions, the stability of the catalytic active components in the particles is higher, they are not easy to fall off or be damaged by friction between the outer edges of the particles, the active life is longer, and the catalytic effect is better.
[0032] It should be noted that the compactness of the composite particles described in this invention is tested using the funnel method, specifically using a Scott volumetric meter. The measuring cup is weighed m0, and the composite particles are allowed to fall freely from a funnel at a fixed height to fill the measuring cup. The cup is then leveled, vertically vibrated until the volume no longer changes, and weighed m1. The compactness is then calculated as (m1-m0) / V, where V is the volume of the measuring cup. This process is repeated three times, and the average value is calculated to obtain the compactness of the composite particles.
[0033] Preferably, the average particle size of the kernel is 1~80μm.
[0034] It should be noted that the average particle size of the kernel described in this invention is confirmed in the following manner: The composite particles were pre-dispersed with ethanol and the samples were prepared. They were then observed using a transmission electron microscope. At 1000X magnification, the composite particles were mapped and analyzed to distinguish the core and shell of the composite particles by elemental distribution and interface profile. Subsequently, the diameter of the core of at least 20 composite particles was measured using measurement software, and the average value was calculated as the average particle size of the core.
[0035] Another object of the present invention is to provide a method for preparing the synergistic catalyst, comprising the following steps: Prepare slurry A by using the precursor of the catalytically active ingredient; Prepare slurry B for the core; Slurry A and slurry B are mixed, and the resulting mixture is adjusted to pH 5-10 and then spray-dried. The resulting powder is then calcined to obtain the synergistic catalyst.
[0036] The synergistic catalyst preparation process described in this invention is simple, has a short operation flow, low equipment requirements, and can achieve industrial-scale mass production.
[0037] Preferably, the catalytically active precursor includes iron-containing compounds, molybdenum-containing compounds, zinc-containing compounds, titanium-containing compounds, potassium-containing compounds, antimony-containing compounds, and nickel-containing compounds.
[0038] In the preparation of the catalytically active ingredient of this invention, the precursor used can be a compound containing relevant elements, and the specific type is not limited. Any precursor commonly used by those skilled in the art is acceptable. For example, the iron-containing compound can be at least one of iron salts and iron oxides, specifically at least one of ferric nitrate, ferric sulfate, ferric chloride, ferric carbonate, ferric acetate, ferric oxide, ferric tetroxide, and ferrous oxide. The zinc-containing compound can be at least one of zinc salts and zinc oxides, specifically at least one of zinc chloride, zinc bromide, zinc iodide, zinc trifluoromethanesulfonate, zinc oxide, zinc nitrate, zinc sulfate, and zinc acetate. The molybdenum-containing compound can be at least one of molybdenum salts and molybdenum trioxide, specifically at least one of ammonium heptamolybdate, molybdenum chloride, molybdenum bromide, ammonium phosphomolybdate, sodium molybdate, and potassium molybdate. At least one of the following: the titanium-containing compound may be at least one of titanium salt, titanium oxide, titanium hydroxide, titanium carbide, and titanium silicide; the titanium salt may include titanium chloride; the titanium oxide may include at least one of titanium dioxide, titanium trioxide, and titanium monoxide; the potassium-containing compound may include a potassium salt, specifically at least one of potassium chloride, potassium bromide, potassium iodide, potassium nitrate, potassium sulfate, and potassium acetate; the antimony-containing compound may be at least one of antimony oxide, antimony sulfide, and antimony salt, specifically at least one of antimony trioxide, antimony tetroxide, antimony trisulfide, antimony pentasulfide, potassium antimonate, lithium antimonyate, and sodium pyroantimonate; and the nickel-containing compound may be at least one of nickel salt and nickel oxide, specifically at least one of nickel chloride, nickel bromide, nickel acetate, nickel trifluoromethanesulfonate, nickel nitrate, and 1,2-bis(diphenylphosphine)ethanedichloride.
[0039] Preferably, a carrier precursor is also added to the slurry A, and the carrier precursor includes at least one of silica sol and alumina sol.
[0040] Specifically, the solid content of the carrier precursor in slurry A is 10~50wt%.
[0041] Specifically, the average particle size of the carrier precursor is 10~150 nm.
[0042] More preferably, the mass content of the carrier precursor in the slurry A is 1~10%.
[0043] Preferably, the specific preparation method of the slurry A is as follows: the catalytic active ingredient precursor is placed in an acidic solution, the pH of the resulting mixture is adjusted to 0.5~3 and stirred, and then the carrier precursor is added and mixed to obtain the slurry A.
[0044] Preferably, the slurry B comprises a core and a dispersing crosslinking agent, wherein the dispersing crosslinking agent comprises at least one of tetrabutylammonium bromide, tetrabutylammonium chloride, hexadecylammonium bromide, octadecylammonium bromide, polyvinyl alcohol, acrylic acid, acrylate, sodium polynaphthalene methanol sulfonate, and potassium polynaphthalene methanol sulfonate.
[0045] More preferably, the core is also etched before the slurry B is prepared.
[0046] More preferably, the etching treatment can be acid etching or alkaline etching. There is no specific limitation on the specific etching process. Those skilled in the art can implement it according to common acid etching and alkaline etching methods for inorganic oxides. For example, the core is compounded with alcohol, and then 0.1-1% of the total mass of the compound is added to an acid solution or alkaline solution and ultrasonically treated at 40-80°C for 10-30 minutes, followed by drying. Other common etching methods and steps can also be used. The etching treatment can further improve the surface roughness of the core. Without affecting the overall structural integrity of the core, those skilled in the art can further improve the connection between the core and the shell during the subsequent preparation of synergistic catalysts through this treatment.
[0047] Preferably, in the slurry B, the mass percentage of the dispersing crosslinking agent is 0.001~10%, and the mass percentage of the core is 2~60%.
[0048] Preferably, when slurry A and slurry B are mixed, the mass ratio of slurry A to slurry B is (0.5~20):1.
[0049] Preferably, during the spray drying process, the mixed slurry is first pumped into the spray dryer using a peristaltic pump. The peristaltic pump speed is 10-80 mL / min, the inlet air temperature is 80-250℃, the outlet air temperature is 80-110℃, the atomization pressure is 0.2-0.6 MPa, the atomization speed is 12000-25000 rpm, and the drying air flow rate is 0.5-1.2 m³ / min. 3 min -1 .
[0050] It should be noted that the synergistic catalyst described in this invention can be controlled during the preparation process by adjusting the feed rate, air inlet temperature, and atomization speed during spray drying. For example, when the feed rate is increased within a certain range, the compactness of the composite particles in the synergistic catalyst increases accordingly. Within a certain range, the compactness increases with the increase of air inlet speed and atomization speed, but it will decrease to a certain extent when it is in a higher range. This is not specifically limited, and those skilled in the art can also use other methods to control it.
[0051] Preferably, the calcination treatment is carried out in an air atmosphere at a temperature of 400~1000℃ for 1~8 hours.
[0052] The preparation method of the present invention can further improve the bonding strength between the core and the shell and the size uniformity of the particles in the product. At the same time, the operation steps are simple and the particle size and compactness of the resulting composite particles are highly controllable. For example, in this scheme, the particle size of the composite particles can be controlled by the particle size of the core, while the compactness can be controlled by parameters during spray drying. However, it is not limited to this. Those skilled in the art can also use other methods, such as the concentration ratio of slurry A or B, to control the product parameters. As long as the obtained product can achieve the expected particle size and compactness, it is acceptable.
[0053] Another object of the present invention is to provide the application of the synergistic catalyst in the simultaneous preparation of acrylonitrile and hydrogen cyanide in a fluidized bed process.
[0054] Another object of the present invention is to provide a method for simultaneously preparing acrylonitrile and hydrogen cyanide using a fluidized bed process, comprising the following steps: Propylene, ammonia, and flash-evaporated methanol are mixed and then fed into a fluidized bed reactor containing the main catalyst and the synergistic catalyst described in this invention. Hot air is introduced and the reaction is carried out to obtain acrylonitrile and hydrogen cyanide.
[0055] Based on the use of the synergistic catalyst described in this invention, the method only requires directly mixing the materials and feeding them into a fluidized bed reactor for reaction, which can quickly and effectively obtain acrylonitrile and hydrogen cyanide products in high yield. In this reaction, the yield ratio of the two products can be truly controlled. Those skilled in the art can simply adjust the reaction conditions during the reaction in the fluidized bed reactor according to actual needs to control the yield of the two products, effectively improving the cost-effectiveness of the products.
[0056] Preferably, the temperature at which the propylene, ammonia, and flash-evaporated methanol are mixed is 80-200°C, and the temperature of the hot air is 80-200°C. Preferably, the temperature of the fluidized bed reactor is 400~480℃ and the pressure is 0.02~0.1MPa.
[0057] In the method described in this invention, the temperature and pressure settings of the fluidized bed reactor can effectively regulate the yield of acrylonitrile and hydrogen cyanide in the obtained product to achieve the required product ratio, but it is not limited to this. Those skilled in the art can also use other methods to regulate it.
[0058] Preferably, the volume ratio of methanol to propylene is (0.1~1):1.
[0059] Preferably, the ratio of the sum of the volumes of methanol and propylene to the volume of ammonia is 1:(1~3).
[0060] Preferably, the ratio of the sum of the volumes of methanol and propylene to the volume of hot air is 1:(8~20).
[0061] In the solution described in this invention, the proportion of added materials can also be used to control the yield of the final product, but it is not limited to this. Those skilled in the art can also use other methods to control it.
[0062] The beneficial effects of this invention are that it provides a synergistic catalyst by constructing a core-shell structure and introducing specific catalytic elements, while controlling the size and density of the product. When this product is used to produce acrylonitrile and hydrogen cyanide, it is not only fully compatible with existing fluidized bed process systems, but also has low operation difficulty and simple process. Furthermore, the acrylonitrile and hydrogen cyanide produced have high yields, and the output ratio can be controlled according to actual needs. Detailed Implementation
[0063] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.
[0064] Example 1 The embodiments of the synergistic catalyst, its preparation method, and its application described in this invention include the following steps: Preparation of synergistic catalysts: Prepare slurry A by using the precursor of the catalytically active ingredient; The catalytically active precursors include ferric nitrate nonahydrate, ammonium heptamolybdate tetrahydrate, zinc nitrate hexahydrate, titanium dioxide, potassium nitrate, antimony trioxide, and nickel nitrate hexahydrate. The specific preparation steps for slurry A are as follows: Each catalytic active component precursor was compounded according to the elemental mass ratio (Fe:Mo:Zn:Ti:K:Sb:Ni=32:13:4:2:1.5:1:0.5) and added to 500g of water. The resulting mixture was pHed to 1 with hydrochloric acid. Then, 80g of silica sol with a solid content of 40% and an average particle size of 10nm was added and stirred for 20min to obtain slurry A with a silica sol mass content of 4wt%. Prepare slurry B for the core; Core pretreatment: 100g of silica particles with an average particle size of 5μm were placed in 100g of hydrochloric acid with a mass concentration of 0.2%, and 100g of n-butanol were added and mixed. The mixture was then ultrasonically treated at 40℃ for 30min, followed by washing and drying. The specific preparation steps for slurry B are as follows: The pretreated kernel and 8g of crosslinking dispersant (a mixture of tetrabutylammonium bromide and polyvinyl alcohol in a mass ratio of 1:1) were dispersed in 500g of water and stirred for 30min to obtain slurry B, with the kernel having a mass percentage of 15%. Slurry A and slurry B were mixed at a ratio of 3.5:1. The resulting mixture was adjusted to pH 6 with ammonia before being spray-dried. The parameters were controlled as follows: peristaltic pump speed 60 mL / min, inlet air temperature 180℃, outlet air temperature 105℃, atomization pressure 0.2 MPa, atomization speed 18000 rpm, and drying air flow rate 0.6 m³ / min. 3 min -1 The obtained powder was heated to 600°C in air and calcined for 2 hours to obtain the synergistic catalyst.
[0065] Fluidized bed process steps: Propylene, ammonia, and flash-evaporated methanol are mixed in a mixing tank at 180°C, and then fed into a fluidized bed reactor containing 400g of the main catalyst XYA-5 and 100g of the synergistic catalyst prepared in this embodiment. Hot air at 180°C is introduced and the reaction is carried out. During the reaction, the temperature of the fluidized bed reactor is set at 430°C and the pressure is 0.03MPa, thus obtaining acrylonitrile and hydrogen cyanide.
[0066] The volume ratio of propylene to methanol is 4:1, the volume ratio of the sum of methanol and propylene to ammonia is 1:1.2, and the volume ratio of the sum of methanol and propylene to hot air is 1:12.
[0067] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1. As can be seen from the actual element mass measurement ratio, it is basically the same as the pre-prepared measurement ratio.
[0068] Example 2 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Each catalytic active component precursor was compounded according to the elemental stoichiometric ratio and added to 500g of water. The resulting mixture was pHed to 2 with hydrochloric acid. Then, 80g of aluminum sol with a solid content of 30% and an average particle size of 150nm was added and stirred for 20min to obtain slurry A with an aluminum sol mass content of 3.5wt%. Prepare slurry B for the core; Pretreatment of the core: 100g of aluminum oxide particles with an average particle size of 6μm were placed in 100g of hydrochloric acid with a mass concentration of 0.1%, and 100g of n-butanol were added and mixed. The mixture was then ultrasonically treated at 40℃ for 30min, followed by washing and drying. The specific preparation steps for slurry B are as follows: The pretreated kernel and 10g of crosslinking dispersant (a mixture of octadecyl ammonium bromide and acrylate in a mass ratio of 1:1) were dispersed in 500g of water and stirred for 30min to obtain slurry B, with the kernel having a mass percentage of 20%.
[0069] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0070] Example 3 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: The kernel is not preprocessed.
[0071] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0072] Examples 4-6, Example 13 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: The dosage ratio of the added catalytically active ingredients varies.
[0073] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0074] In Example 4, ferric chloride was used as the iron-containing compound, molybdenum trioxide as the molybdenum-containing compound, zinc bromide as the zinc-containing compound, titanium hydroxide as the titanium-containing compound, sodium pyroantimonate pentahydrate as the antimony-containing compound, potassium sulfate as the potassium-containing compound, and nickel oxide as the nickel-containing compound.
[0075] Example 7 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: The core uses silica particles with an average particle size of 1 μm.
[0076] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0077] Example 8 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: The core uses silica particles with an average particle size of 40 μm.
[0078] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0079] Example 9 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: The core uses silica particles with an average particle size of 65 μm.
[0080] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0081] Example 10 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Spray dryer parameter control: peristaltic pump speed is 30 mL / min, and atomization speed is 12000 rpm.
[0082] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0083] Example 11 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Spray dryer parameter control: peristaltic pump speed 50mL / min, atomization pressure 0.4Mpa.
[0084] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0085] Example 12 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Spray dryer parameter control: peristaltic pump speed is 20mL / min, and inlet air temperature is 130℃.
[0086] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 1.
[0087] Examples 14-17 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Fluidized bed process steps: Propylene, ammonia, and flash-evaporated methanol are mixed in a mixing tank at 180°C, and then fed into a fluidized bed reactor containing 450g of the main catalyst XYA-5 and 150g of the synergistic catalyst prepared in this embodiment. Hot air at 180°C is introduced and the reaction is carried out. During the reaction, the temperature of the fluidized bed reactor is set at 440°C and the pressure is 0.04MPa, thus obtaining acrylonitrile and hydrogen cyanide.
[0088] The ratio of the sum of the volumes of methanol and propylene to the volume of ammonia is 1:1.5, and the ratio of the sum of the volumes of methanol and propylene to the volume of hot air is 1:15.
[0089] In Example 14, the volume ratio of propylene to methanol was 10:1; in Example 15, the volume ratio of propylene to methanol was 7:1; in Example 16, the volume ratio of propylene to methanol was 4:1; and in Example 17, the volume ratio of propylene to methanol was 1:1.
[0090] Example 18 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Fluidized bed process steps: Propylene, ammonia, and flash-evaporated methanol are mixed in a mixing tank at 120°C, and then fed into a fluidized bed reactor containing 500g of the main catalyst XYA-5 and 50g of the synergistic catalyst prepared in this embodiment. Hot air at 120°C is introduced and the reaction is carried out. During the reaction, the temperature of the fluidized bed reactor is set at 470°C and the pressure is 0.04MPa, thus obtaining acrylonitrile and hydrogen cyanide.
[0091] The volume ratio of propylene to methanol is 10:1, the volume ratio of the sum of methanol and propylene to ammonia is 1:1.1, and the volume ratio of the sum of methanol and propylene to hot air is 1:10.
[0092] Example 19 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Fluidized bed process steps: Propylene, ammonia, and flash-evaporated methanol are mixed in a mixing tank at 180°C, and then fed into a fluidized bed reactor containing 400g of the main catalyst XYA-5 and 100g of the synergistic catalyst prepared in this embodiment. Hot air at 180°C is introduced and the reaction is carried out. During the reaction, the temperature of the fluidized bed reactor is set at 470°C and the pressure is 0.09MPa, thus obtaining acrylonitrile and hydrogen cyanide.
[0093] Example 20 The synergistic catalyst, its preparation method, and its application embodiments described in this invention differ from Example 1 only in that: Fluidized bed process steps: Propylene, ammonia, and flash-evaporated methanol are mixed in a mixing tank at 180°C, and then fed into a fluidized bed reactor containing 280g of the main catalyst XYA-5 and 280g of the synergistic catalyst prepared in this embodiment. Hot air at 180°C is introduced and the reaction is carried out. During the reaction, the temperature of the fluidized bed reactor is set at 440°C and the pressure is 0.04MPa, thus obtaining acrylonitrile and hydrogen cyanide.
[0094] The volume ratio of propylene to methanol is 10:1, the volume ratio of the sum of methanol and propylene to ammonia is 1:1.5, and the volume ratio of the sum of methanol and propylene to hot air is 1:15.
[0095] Comparative Example 1 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain iron-containing compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the Si element contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0096] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0097] Comparative Example 2 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain molybdenum compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the Si element contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0098] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0099] Comparative Example 3 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain zinc compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the Si element contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0100] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0101] Comparative Example 4 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain titanium compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the Si element contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0102] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0103] Comparative Example 5 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain antimony compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the amount of Si contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0104] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0105] Comparative Example 6 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain potassium compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the Si element contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0106] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0107] Comparative Example 7 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain nickel-containing compounds. When preparing slurry A, it is replaced by silica sol with an equal silicon elemental ratio (based on the Si element contained in the silica sol). The addition ratio of the catalytic active ingredient is different.
[0108] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0109] Comparative Example 8 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain potassium-containing compounds, but instead contains sodium carbonate as the sodium-containing compound, and the dosage ratio of the added catalytic active ingredient varies.
[0110] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0111] Comparative Example 9 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain nickel-containing compounds, but instead contains magnesium oxide as a magnesium-containing compound, and the addition ratio of the catalytic active ingredient varies.
[0112] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0113] Comparative Example 10 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The precursor of the catalytic active ingredient does not contain antimony compounds, but instead uses calcium chloride as the calcium-containing compound, and the addition ratio of the catalytic active ingredient varies.
[0114] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0115] Comparative Example 11 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The core uses silica particles with an average particle size of 0.2 μm.
[0116] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0117] Comparative Example 12 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The core uses silica particles with an average particle size of 80 μm.
[0118] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0119] Comparative Example 13 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The spray dryer parameters are controlled as follows: peristaltic pump speed is 5 mL / min, atomization speed is 10000 rpm, and inlet air temperature is 120℃.
[0120] The chemical composition and particle size D of the synergistic catalystv50 The density is shown in Table 2.
[0121] Comparative Example 14 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: The spray dryer parameters are controlled as follows: peristaltic pump speed is 100 mL / min, atomization speed is 20000 rpm, and inlet air temperature is 205℃.
[0122] The chemical composition and particle size D of the synergistic catalyst v50 The density is shown in Table 2.
[0123] Comparative Example 15 A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: Preparation of synergistic catalysts: The precursor of the catalytically active ingredient is formulated into a slurry; The catalytically active precursors include ferric nitrate nonahydrate, ammonium heptamolybdate tetrahydrate, zinc nitrate hexahydrate, titanium dioxide, potassium nitrate, antimony trioxide, and nickel nitrate hexahydrate. The specific steps for preparing the slurry are as follows: Each catalytic active component precursor was compounded according to the elemental stoichiometric ratio and added to 500g of water. The resulting mixture was pHed to 1 with hydrochloric acid. Then, 80g of silica sol with a solid content of 40% and an average particle size of 10nm was added and stirred for 20min to obtain a slurry with a silica sol mass content of 4wt%. The slurry was directly spray-dried using the following controlled parameters: peristaltic pump speed 60 mL / min, inlet air temperature 180℃, outlet air temperature 105℃, atomization pressure 0.2 MPa, atomization speed 18000 rpm, and drying air flow rate 0.6 m³ / min. 3 min -1 The obtained powder was heated to 600°C in air and calcined for 2 hours to obtain the synergistic catalyst.
[0124] Blank example A synergistic catalyst, its preparation method, and its application differ from Example 1 only in that: In the fluidized bed process system, only 500g of the main catalyst is added, and no synergistic catalyst is added.
[0125] Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this invention are commercially available. The results are shown in Tables 1 and 2.
[0126] Table 1 Table 2 Example of effect The yields of acrylonitrile and hydrogen cyanide were calculated for each example and comparative example: Acrylonitrile yield test method: Weigh a certain amount of liquid sample from the obtained material sampling bottle, use 2-butanone as internal standard, mix well, and analyze by gas chromatography (chromatographic model: Thermo Scientific TRACE 1600, chromatographic column model: TG-WAXMS A). Then calculate the amount of acrylonitrile after reaction based on the weighed volume. Then acrylonitrile yield = n (amount of acrylonitrile) / (amount of propylene) × 100%.
[0127] Hydrogen cyanide yield test method: The obtained material is titrated with silver nitrate standard solution in an alkaline potassium iodide solution to remove cyanide ions. The endpoint is reached when the first drop of excess silver nitrate reacts with potassium iodide to form an insoluble precipitate after all cyanide ions in the solution have been removed. The hydrogen cyanide content in the sample is calculated based on the amount of silver nitrate consumed. Hydrogen cyanide yield = n (amount of hydrogen cyanide) / ((amount of propylene) × 3 + (amount of methanol)) × 100%.
[0128] The test results are shown in Table 3.
[0129] Table 3 As can be seen from the table above, the synergistic catalyst described in this invention has ideal performance. When applied to a fluidized bed process system for one-step preparation of acrylonitrile and hydrogen cyanide, the yield ratio of the two products can be controlled based on the setting of process parameters, as shown in Examples 14-17. With the adjustment of the material ratio, the yields of acrylonitrile and hydrogen cyanide change. Those skilled in the art can adjust the yield at any time based on factors such as commodity value and cost. Furthermore, the synergistic catalyst can ensure that the yields of both products are at a high level when applied, with the yield of acrylonitrile reaching over 73% and the yield of hydrogen cyanide reaching over 12%. This is mainly due to the core-shell structure of the component, the introduction of specific catalytically active components, and the control of the particle size and compactness of the composite particles. In contrast, Comparative Examples 1-7 were prepared with incomplete catalytic active components, lacking one of them. While Comparative Examples 8-10 also contained catalytic active components, the types were not corresponding. When used, these products were difficult to achieve the high catalytic yield of both products compared to the products in the examples, and even showed no significant yield improvement compared to the blank example without the introduction of a synergistic catalyst. As can be seen from Examples 1, 7-9, and Comparative Examples 11 and 12, if the particle size of the synergistic catalyst is too large or too small, it will affect the catalytic activity of the product, and the yield of acrylonitrile and / or hydrogen cyanide will decrease. As can be seen from Examples 1, 10-12, and Comparative Examples 13-14, in addition to particle size, the density also affects the structural stability of the particles, the dispersibility when applied to a fluidized bed, and the catalytic activity, and needs to be controlled within a specific range of 0.8-1.8 mg / L. As can be seen from Comparative Example 15, when no core-shell structure is set, the catalytic activity is rapidly lost due to the internal collapse of the synergistic catalyst during use, resulting in almost no difference compared with the blank product. This indicates that the setting of the core-shell structure is very critical.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A synergistic catalyst, characterized in that, Includes composite particles, said composite particles comprising a core and a shell; The core comprises inorganic oxides; The outer shell includes catalytically active components; the catalytically active components include iron, molybdenum, zinc, titanium, potassium, antimony, and nickel. The particle size D of the composite particles v50 The size ranges from 20 to 100 μm, and the density ranges from 0.8 to 1.8 g / mL.
2. The synergistic catalyst as described in claim 1, characterized in that, In the core, the inorganic oxide includes at least one of silicon dioxide and aluminum oxide, and / or the shell further includes a carrier, which includes at least one of silicon dioxide and aluminum oxide.
3. The synergistic catalyst as described in claim 1, characterized in that, The synergistic catalyst comprises the following elements in parts by weight: Si and / or Al 5~25 parts, Fe 20~45 parts, Mo 1~25 parts, Zn 1~15 parts, Ti 1~15 parts, K 1~12 parts, Sb 0.1~12 parts, Ni 0.1~12 parts.
4. The synergistic catalyst as described in claim 3, characterized in that, In the synergistic catalyst, the metal element in the catalytically active component exists in the form of metal oxides and / or metal salts, and / or, the synergistic catalyst comprises, by weight, the following elements per 100 parts: 10-20 parts Si and / or Al, 25-40 parts Fe, 5-20 parts Mo, 1-10 parts Zn, 1-10 parts Ti, 1-9 parts K, 0.1-9 parts Sb, 0.1-9 parts Ni, and 15-40 parts of valence equilibrium elements.
5. The synergistic catalyst as described in claim 4, characterized in that, The synergistic catalyst comprises, per 100 parts, the following elements by weight: 12-18 parts Si and / or Al, 27-35 parts Fe, 12-16 parts Mo, 2-5 parts Zn, 2-4 parts Ti, 1.2-4 parts K, 0.5-5 parts Sb, 0.3-6 parts Ni, and 16-35 parts of valence equilibrium elements.
6. The synergistic catalyst as described in claim 1, characterized in that, The particle size D of the composite particles v50 The particle size is 40~80μm, and / or the density of the composite particles is 1~1.5 g / mL.
7. The method for preparing the synergistic catalyst according to any one of claims 1 to 6, characterized in that, Includes the following steps: Prepare slurry A by using the precursor of the catalytically active ingredient; Prepare slurry B for the core; Slurry A and slurry B are mixed, and the resulting mixture is adjusted to pH 5-10 and then spray-dried. The resulting powder is then calcined to obtain the synergistic catalyst.
8. The method for preparing the synergistic catalyst as described in claim 7, characterized in that, The catalytically active precursors include iron-containing compounds, molybdenum-containing compounds, zinc-containing compounds, titanium-containing compounds, potassium-containing compounds, antimony-containing compounds, and nickel-containing compounds.
9. The method for preparing the synergistic catalyst as described in claim 7, characterized in that, The core is also etched before slurry B is prepared.
10. The application of the synergistic catalyst according to any one of claims 1 to 6 in the simultaneous preparation of acrylonitrile and hydrogen cyanide in a fluidized bed process.
11. A method for simultaneously preparing acrylonitrile and hydrogen cyanide using a fluidized bed process, characterized in that, Includes the following steps: Propylene, ammonia, and flash-evaporated methanol are mixed and then fed into a fluidized bed reactor containing a main catalyst and a synergistic catalyst as described in any one of claims 1 to 6. Hot air is introduced and the reaction is carried out to obtain acrylonitrile and hydrogen cyanide.
12. The method for simultaneously preparing acrylonitrile and hydrogen cyanide using a fluidized bed process as described in claim 11, characterized in that, The temperature of the fluidized bed reactor is 400~480℃, and / or the pressure of the fluidized bed reactor is 0.02~0.1MPa.
13. The method for simultaneously preparing acrylonitrile and hydrogen cyanide using a fluidized bed process as described in claim 11, characterized in that, The volume ratio of methanol to propylene is (0.1~1):1, and / or the volume ratio of the sum of the volumes of methanol and propylene to the volume of ammonia is 1:(1~3), and / or the volume ratio of the sum of the volumes of methanol and propylene to the volume of hot air is 1:(8~20).
